ChemInform Abstract: Asymmetric Synthesis of Cyclopropanes with a Monofluorinated Quaternary Stereocenter. Issue 10 (7th March 2013) - Ivashkin, Pavel; Couve‐Bonnaire, Samuel; Jubault, Philippe; Pannecoucke, Xavier
Abstract Zn/LiCl‐mediated treatment of the oxazolidinone (I) with electron‐deficient alkenes results in efficient and stereoselective formation of polysubstituted monofluorinated cyclopropanes.